ANALISIS LAPORAN SUMBER DAN PENYALURAN DANA KEBAJIKAN PADA BANK SYARIAH INDONESIA PERIODE ENAM BULAN PERTAMA TAHUN 2021 - Safa Kurnia Putri; Nabila Amalia; Larassandy Utami; M. Alija Izzetbegovic Malak; Andi Amri (IZZI: Jurnal Ekonomi Islam, 2022)
Virtue Funds and Zakat Funds are referred to as trusts in the form of deposited funds that will be distributed to parties entitled to receive zakat or to social institutions. Before the funds are distributed, it will add to the value of assets in Islamic banks. The purpose of this report analysis is to adjust the report on the benevolence fund of Bank Syariah Indonesia in the period from January to June with the report stated in PSAK No. 101. This analysis uses a qualitative method that reveals the income of the benevolence fund at Bank Syariah Indonesia (BSI). The results showed that the number of Qardhul Hasan funds or sources of benevolence funds at Bank Syariah Indonesia in 2020 was more than in the early 2021 period. Bank Syariah Indonesia distributed these benevolent funds for social activities, such as donations for natural disasters, donations for religious activities, institutional development assistance. education, construction of places of worship, and so on.